Mitigating business risks in the culinary supply chain: An empirical study in Bangkalan District - Hemada, Syah Firda Lula; Hayati, Mardiyah (Universitas Sultan Ageng Tirtayasa, 2024)
Most Medium, Small, and Micro Enterprises (MSMEs) in the culinary sector are experiencing the fastest growth and increasing trends in demand and income, indicating the potential for business expansion. However, many MSMEs have encountered several problems in their supply chain that could jeopardize business continuity. The objectives of this research are: 1) to identify risk events and risk sources (risk agents) and prioritize them; and 2) to determine the mitigation actions (preventive actions) that MSMEs need to undertake to minimize risks. The identification of risk events is conducted using the SCOR (Supply Chain Operation Reference) approach, while data analysis employs the HOR (House of Risk) method. It is revealed that there are 38 risk events with 24 risk sources. From the three priority risk sources, 8 mitigation actions were developed, with 3 priority mitigation actions identified: determining supplier criteria, establishing minimum order time regulations, and maintaining records related to production raw material stocks.